Association between allergic or autoimmune diseases and incidence of endometriosis: A nested case‐control study using a health insurance claims database. (9th August 2021) - Yoshii, Erika; Yamana, Hayato; Ono, Sachiko; Matsui, Hiroki; Yasunaga, Hideo
Abstract: Problem: Immune responses were reported to be associated with the pathogenesis of endometriosis. However, previous studies of an association between allergic or autoimmune diseases and endometriosis have reported inconsistent results. We investigated the association between allergic or autoimmune diseases and the incidence of endometriosis. Method of study: Using a large‐scale health insurance claims database in Japan, we identified patients with endometriosis diagnosed between April 2011 and August 2018. For each case, we identified up to four controls with the same age and registration month. Conditional logistic regression analyses were conducted to evaluate the incidence rate ratio (IRR) of endometriosis in women with allergic diseases (asthma, allergic rhinitis, urticaria, atopic dermatitis, allergic conjunctivitis, and type 1 allergies combined), systemic lupus erythematosus, and rheumatoid arthritis compared with women without these diseases. Results: We identified 30 516 cases with endometriosis and 120 976 control participants. Mean age at registration was 30 years. There were significant positive associations between type 1 allergy and endometriosis (IRR, 1.10; 95% confidence interval, 1.06–1.13) and between rheumatoid arthritis and endometriosis (IRR, 1.31; 95% confidence interval, 1.05–1.64). Diagnosis of systemic lupus erythematosus was not associated with increased incidence of endometriosis. Among the different allergic diseases, allergic rhinitis, urticaria, and allergic conjunctivitis were associated with the increased incidence. Conclusion: Several allergic diseases were associated with an increased incidence of endometriosis. A higher incidence was also observed in patients with rheumatoid arthritis. Further studies are warranted to elucidate the influence of immune responses on the development of endometriosis.